Anti-estrogenic and anti-aromatase activities of citrus peels major compounds in breast cancer - Dina M. El-Kersh (Nature Portfolio, 2021)
Abstract Estrogen signaling is crucial for breast cancer initiation and progression. Endocrine-based therapies comprising estrogen receptor (ER) modulators and aromatase inhibitors remain the mainstay of treatment. This study aimed at investigating the antitumor potential of the most potent compounds in citrus peels on breast cancer by exploring their anti-estrogenic and anti-aromatase activities. The ethanolic extract of different varieties of citrus peels along with eight isolated flavonoids were screened against estrogen-dependent breast cancer cell lines besides normal cells for evaluating their safety profile. Naringenin, naringin and quercetin demonstrated the lowest IC50s and were therefore selected for further assays. In silico molecular modeling against ER and aromatase was performed for the three compounds. In vivo estrogenic and anti-estrogenic assays confirmed an anti-estrogenic activity for the isolates. Moreover, naringenin, naringin and quercetin demonstrated in vitro inhibitory potential against aromatase enzyme along with anticancer potential in vivo, as evidenced by decreased tumor volumes. Reduction in aromatase levels in solid tumors was also observed in treated groups. Overall, this study suggests an antitumor potential for naringenin, naringin and quercetin isolated from citrus peels in breast cancer via possible modulation of estrogen signaling and aromatase inhibition suggesting their use in pre- and post-menopausal breast cancer patients, respectively.